Planning for Maintenance and Repair of Continuous Ship Unloader Using the IRRO Method - Syamsul Hadi; Alfarizi Al Azis; Vinan Viyus; Etik Puspitasari; Ahmad Hanif Firdaus; Andri Setiawan (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The problem faced is damage, especially to the screw conveyor from the Continuous Ship Unloader (CSU) as a dry bulk material transfer equipment (phosphate rock) which is taken from the ship's hold which is flowed by a screw conveyor followed by the belt conveyor to the material warehouse to be processed into a type of fertilizer. The purpose of planning is to obtain a schedule and estimated cost of maintenance and repair of CSU for the period 2022 to 2025, and to obtain the ratio of maintenance-repair costs to the profit of the machine. Planning methods uses the IRRO (Inspection, Replace, Repair, and Overhoul) method include data collection of machine maintenance history and component breakdowns, checking CSU specifications, making a list of component life predictions and component prices, predicting costs and duration of component dissasembly, screw conveyor repair, maintenance and repair scheduling, and maintenance and repair cost estimates. The real results of planning in the form of a maintenance and repair schedule for the period of 2022 to 2025; maintenance and repair costs respectively for the years 2022 to 2025 are IDR 136,873,000; IDR 335,986,000; IDR 160,687,000; and IDR 464,733,000; and the ratio between maintenance costs to profit for the years 2022 to 2025 is 0.51, 1.22, 0.57, and 1.63 which means the machine is still fit for use without the need for refurbishment because it is still prospective.